Nuclear βII-Tubulin and its Possible Utility in Cancer Diagnosis, Prognosis and Treatment - Ludueña, Richard F.; Walss-Bass, Consuelo; Portyanko, Anna; Guo, Jiayan; Yeh, I-Tien (Frontiers in Cell and Developmental Biology, 2022)
Microtubules are organelles that usually occur only in the cytosol. Walss et al. (1999) discovered the βII isotype of tubulin, complexed with α, in the nuclei of certain cultured cells, in the form of a filament. When fluorescently labeled tubulins were microinjected into the cells, only αβII appeared in the nucleus, and only after one cycle of nuclear disassembly and reassembly. It appeared as if αβII does not cross the nuclear envelope but is trapped in the nucleus by the re-forming nuclear envelope in whose reassembly βII may be involved. βII is present in the cytoplasm and nuclei of many tumor cells. Normal tissues that expressed βII rarely had βII in their nuclei. It is possible that βII is involved in nuclear reassembly and then disappears from the nucleus. In tumor cells, which divide more frequently, βII may be more commonly observed in the nuclei than in normal tissues. Ruksha et al (2018) observed that patients whose colon cancer cells in the invasive front showed no βII had a median survival of about 5.5 years, which was more than halved if they had cytosolic βII and further lessened if they had nuclear βII, suggesting that the presence and location of βII in biopsies could be a useful prognostic indicator and also that βII may be required for cancer progression. Yeh and Luduena (2004) observed that many tumors were surrounded by non-cancerous cells exhibiting cytosolic and nuclear βII, suggesting a signaling pathway that causes βII to be synthesized in nearby cells and localized to their nuclei. βII could be useful in cancer diagnosis, since the presence of βII in non-cancerous cells could indicate a nearby tumor. Investigation of this pathway might reveal novel targets for chemotherapy. Another possibility would be to combine αβII with CRISPR-Cas9. This complex would likely enter the nucleus of a cancer cell and, if guided to the appropriate gene, might destroy the cancer cell or make it less aggressive; possible targets will be discussed here. The possibilities raised here about the utility of βII in cancer diagnosis, prognosis, biology and therapy may repay further investigation.